Exercises for the development of the Mexican ballad of bases in the Stage of Special Preparation in the Baseball - Pablo Terry-Álvarez; Grettel Polo-Bugallo; Frank Leonel Valdés-Fong (Universidad de Guantánamo, 2018)
This work has as end the elaboration of exercises for the development of the Mexican ballad of bases in the Baseball, where one kept in mind the four distances determinant for the annotation in the baseball, it is the case from the home career to first base, of first base to third base, of second base to home and from third base to home, showing the interconnection of the capacities in an ordinary microcell inside the stage of special preparation. The used theoretical methods: Historical-logical, Analysis-synthesis, Inductive-deductive and the Empiric ones the documental revision.